AMS analyses of I-129 from the Fukushima Daiichi nuclear accident in the Pacific Ocean waters of the Coast La Jolla – San Diego, USA. Issue 5 (22nd April 2015) - Stan-Sion, C.; Enachescu, M.; Petre, A. R.
Abstract : This paper presents the results of an experimental study we performed by using the Accelerator Mass Spectrometry (AMS) method with iodine 129 ( T 1/2 = 15.7 My), to determine the increase of the radionuclide content in the USA West Pacific Coast waters, two years after the March 2011 Fukushima Daiichi nuclear power plant accident. Abstract : This paper presents the results of an experimental study we performed by using the Accelerator Mass Spectrometry (AMS) method with iodine 129 ( T 1/2 = 15.7 My), to determine the increase of the radionuclide content in the USA West Pacific Coast waters, two years after the March 2011 Fukushima Daiichi nuclear power plant accident. The collection of the water samples took place between April and July 2013 at regular intervals of time, from the Pacific Ocean, at the cove of La Jolla, San Diego, USA. The results of the experiments showed a significant increase of the radionuclide concentration during the late spring of 2013. Compared to the isotopic ratio 129 I/ 127 I, measured at a 40 km distance, offshore of Fukushima and immediately after the accident, our results show an increase on the USA West Coast that was more than a 2.5 factor higher. Also, compared with the pre-Fukushima background values, our results show an isotopic ratio of about two orders of magnitude higher. A distinct feature of the reconstructed radioactive plume was that it traveled with a speed of 12 cm s −1, which we estimated and is consistent with the zonal speed in the Pacific. We coupled our 129 I results with the measurements from the June 2011 KOK cruise and we derived the levels of activity for 3 H and 137 Cs. On the USA West Coast, they did not exceed the international regulatory limits.